Survei Rumah Sehat di Kota Yogyakarta, Tahun 2008 - Sigid Sudaryanto; Siti Hani Istiqomah; Indah Werdiningsih (Poltekkes Kemenkes Yogyakarta, 2009)
House is one of primary needs for people. As a shelter, a house must fulfill four conditions, i.e. physiological and psychological aspects, and disease and accident prevention. The survey was conducted to collect data and information on the conditon of houses in Yogyakarta City by observing house components, sanitation facilites and healthy behaviours, and was held in November and December 2008. The sample were 1050 households in 11 community health center’s serving areas. In general, the majority of households: are categorizedas healthy and quite healthy; have adequate ventilation, smoke emition hole, and natural lighting; have adequate clean water, and excreta disposal facilities; and have adequate behaviours related to prevention of diarrhea and acute respiratory infection. The survey also showed descriptively that the condition of houses corresponded with the incident of both diseases.